Carbon Nanotubes - Current Progress of Their Polymer Composites 2016
DOI: 10.5772/62508
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Nanotube Composites as Electromagnetic Shielding Materials in GHz Range

Abstract: Following the development of the new electronic systems and communication networks, the levels of electromagnetic contamination have risen dramatically in the recent years. Every day, new studies appear searching for a way to mitigate the electromagnetic interferences EMI . "t the same time, the rapid evolution of technology forces the field to search for lighter and more efficient materials. The composites using carbon allotropes such as carbon nanotubes and polymers as reinforcement are gaining importance, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 65 publications
0
27
1
Order By: Relevance
“…Gonzalez et al reported that the reflection from CNT and graphene is approximately 10 dB with an absorption of 20 dB. At the same time, ultrathin graphene-based composites have also shown a lower reflection of approximately 10 dB [ 75 , 83 , 84 , 85 ]. According to Zhao et al the EMI shielding of the PVDF/graphene composite was 22.58 dB at a thickness 0.1 mm and electrical conductivity of 6.56 × 10 −3 S·cm −1 [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…Gonzalez et al reported that the reflection from CNT and graphene is approximately 10 dB with an absorption of 20 dB. At the same time, ultrathin graphene-based composites have also shown a lower reflection of approximately 10 dB [ 75 , 83 , 84 , 85 ]. According to Zhao et al the EMI shielding of the PVDF/graphene composite was 22.58 dB at a thickness 0.1 mm and electrical conductivity of 6.56 × 10 −3 S·cm −1 [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, tailoring the fraction and size of pores created on the surface of a conductive compound will help to modulate the phenomenon of electromagnetic reflection. Minimizing reflection, a larger fraction of the radiation will penetrate into the material, being able to dissipate it by absorption …”
Section: Foam‐based Materialsmentioning
confidence: 99%
“…Khan et al reported that both electrical conductivity and permittivity are important factor for the improvement of total shielding effectiveness. On the other hand, It was also reported the small difference in the conductivity caused by the type of CNT . Polymer matrix composites with high electrical conductivity assist in reducing or eradicating the seams in the housing that is the shield.…”
Section: Introductionmentioning
confidence: 99%